Biodegradable nanocomposite of poly(ester-co-carbonate) and cellulose nanocrystals for tough tear-resistant disposable bags. Issue 6 (5th February 2021) - Kim, Hyeri; Jeon, Hyeonyeol; Shin, Giyoung; Lee, Minkyung; Jegal, Jonggeon; Hwang, Sung Yeon; Oh, Dongyeop X.; Koo, Jun Mo; Eom, Youngho; Park, Jeyoung
Abstract : The "3C-tuning" via chemical designing and nanocompositing upgrades mechanical performances of poly(butylene succinate) to a remarkable level with accelerated biodegradation. Abstract : Current sustainable bioplastics need dramatic improvement to become competitive. Herein, we prepared poly(butylene succinate- co -carbonate) nanocomposites with citric acid and cellulose nanocrystals (CNCs). The dimethyl carbonate co-monomer lowers crystallinity and increases elongation; citric acid increases the strength, and the CNCs maximize mechanical performance. Accelerated biodegradation is also favorable for sustainable tough bags.